Suspected phenobarbital-induced pancytopenia in a cat. Issue 1 (May 2020) - Lyraki, Maria; Wilson, Helen
Case summary: A 3-year-old neutered male domestic shorthair cat developed pancytopenia 6 months after starting phenobarbital for treatment of recurrent seizures. The cat was switched from phenobarbital to levetiracetam and complete resolution of the pancytopenia was documented within 10 weeks, consistent with phenobarbital-induced pancytopenia. Relevance and novel information: While phenobarbital is frequently used as the first-line treatment for seizures in cats, phenobarbital-induced feline pancytopenia has not been documented in the veterinary literature before. Based on this case, regular monitoring of the complete blood count in cats receiving long-term phenobarbital treatment should be considered. In cases of persistent or severe haematological abnormalities, further investigations are required and treatment discontinuation may be needed in the absence of other causes of pancytopenia.